2016
DOI: 10.1002/nem.1927
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of legacy QCN for multicast and multiple unicast traffic transmission

Abstract: A multicast congestion control scheme is an interesting feature to control group communication applications such as teleconferencing tools and information dissemination services. This paper addresses a comparison between multiple unicast and multicast traffic congestion control for Carrier Ethernet. In this work, we proposed to study the Quantized Congestion Notification (QCN), which is a Layer 2 congestion control scheme, in the case of multicast traffic and multiple unicast traffic. Indeed, the QCN has recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…However, IEEE 802.1Qau lacks certain qualities because, similar to the IEEE 802.3x, IEEE 802.1Qau was unable to support the priority implementation that was much needed in modern day data centres. IEEE 802.1Qau multicast communication has also been studied in [61,62]. It was shown that in a multiple-bottleneck situation IEEE 802.1Qau occasionally improves fairness issues but it cannot resolve the unfair condition to long-hop flow [62].…”
Section: Cn Schemesmentioning
confidence: 99%
“…However, IEEE 802.1Qau lacks certain qualities because, similar to the IEEE 802.3x, IEEE 802.1Qau was unable to support the priority implementation that was much needed in modern day data centres. IEEE 802.1Qau multicast communication has also been studied in [61,62]. It was shown that in a multiple-bottleneck situation IEEE 802.1Qau occasionally improves fairness issues but it cannot resolve the unfair condition to long-hop flow [62].…”
Section: Cn Schemesmentioning
confidence: 99%
“…One of our previous works compared QCN performance for multicast traffic with that for multiple unicast traffic . While our previous work proposed to solve the feedback implosion problem by setting a high Qeq threshold value (for instance 75% of the queue capacity) , the proposed enhancement for QCN, in this paper, could solve the feedback implosion problem at low Qeq threshold values (25% of the queue capacity). Thus, our proposition for enhancement could fit the recommendation of the QCN standard (i.e.…”
Section: Introductionmentioning
confidence: 99%